Advancing treatment for perihilar cholangiocarcinoma: role of hepatopancreaticoduodenectomy in small-volume centers - Shin, Sang Yun; Jang, Eun Jeong; Kang, Sung Hwa; Park, Eun Hwa; Kim, Kwan Woo (Frontiers in Surgery, 2024)
Hepatopancreaticoduodenectomy (HPD) is a controversial surgical technique for the treatment of perihilar cholangiocarcinoma. This study aimed to clarify the mortality, morbidity, and survival outcomes in patients with perihilar cholangiocarcinoma who underwent HPD at a small-volume hepatobiliary-pancreatic center. This retrospective study included 78 patients with perihilar cholangiocarcinoma who underwent HPD (n = 18) or major liver resection with bile duct resection (n = 60) at our center between October 2013 and December 2022. The primary endpoints were the inhospital morbidity and 90-day mortality rates. The secondary endpoints included the recurrence-free and overall survival rates in both groups. Major complications (Clavien-Dindo grade ≥3) were more common in the HPD group (Group 1, 61.1%) than in the major liver resection group (Group 2; 23.3%, p = 0.03). The 1-, 3-, and 5-year overall survival rates for Groups 1 and 2 were 66.7%, 41.7%, and 27.8% and 79.9%, 44.5%, and 22.7%, respectively (p = 0.89). The 1-, 3-, and 5-year recurrence-free survival rates for Groups 1 and 2 were 64.2%, 53.5%, and 35.6% and 85.3%, 46.8%, and 25.0%, respectively (p = 0.41). Although morbidity and mortality after HPD are higher than those after other surgeries, our findings suggest that HPD is a feasible treatment option for perihilar cholangiocarcinoma, even in small-volume centers. However, meticulous pre-and perioperative evaluation of the patient's overall health status, quality of life, and prospective advantages are required.